Support to content-based image query in object-oriented databases - Traina, Caetano; Traina, Agma J.M.; Dos Santos, Rildo R. [UNESP]; Senzako, Edna Y. (Association for Computing Machinery (ACM), 1998)
This paper presents an Object Manager that stores medical images as a data type of attributes that can be associated to objects, and a support system developed to offer this kind of tool to medical application developers. The purpose of this work is to support the retrieval of images through queries based on the graphical contents of stored images. The usual approach uses icons and textual attributes stored with the images to specify queries. This work uses a novel modeUng technique to define the image data type, by means of which it is possible to decide, before the query itself, the key data of each image that must be extracted from the image when it is stored in the database, allowing faster search when queries are issued. This approach enables building of expansible systems, where new image processing algorithms can be added easily, using its syntactic representation stored through an Image Meta-schema into the application database schema. This work shows how such a system has been implemented, and also a query language used to refer and execute these algorithms from inside the database management system.
Keywords: Data modelling; Digital library; Image database; Medical databases; Object oriented database